Protein Quality of Starter Phase Kalosi Chicken Feed with the Addition of Black Soldier Fly Larvae and Indigofera zollingeriana - Purwanti, Sri; Ahmad, Muhammad Misbah (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
The study aimed to determine the protein quality of the starter phase of free-range chicken feed added with BSF larvae and Indigofera zollingeriana. The ration materials used were commercial feed, yellow corn, rice bran, coconut cake, NaCl, maggot flour, Indigofera flour, CaCO3, premix, turmeric, and L-lysine, DL-methionine, H2SO4, and NaOH. The study used quantitative descriptive analysis by comparing the protein quality and amino acid composition in commercial feeds. The composition of the research ration was P0 = commercial feed, P1 = basal diet + 5% Indigofera flour + 25% maggot flour + 2.5% turmeric flour, P2 = basal diet + 10% Indigofera flour + 20% maggot flour + 2.5% turmeric powder. The results obtained chemical scores, namely P0 (amino acid cysteine = 65.52%), P1 (methionine = 71.79%), and P2 (cysteine = 68.97%) with methionine and cysteine as limiting amino acids. The essential amino acid index values were P0 = 127.96, P1 = 129.62, and P2 = 114.52. the study concluded that the combination of P1 treatment (basal ration, 5% Indigofera flour, 25% maggot flour, and 2.5% turmeric flour) could be used as poultry feed to optimize protein requirements in feed. Keywords: amino acid, amino acid score, chemical score, essential amino acid index